Contraceptive use and decision-making in Guéra, Chad: a mixed-methods study - Allambademel, Vincent de Paul; Abdelaziz, Mahamat; Andrasko, Natalie; Goumbo, Bongo; Madjigoto, Robert; Ngarmbatedjimal, Alexis; Noubadjim, Solal; Tamira, Salomon; Varelis, Theodora; Vourbane, Katchebe; Casey, Sara E. (Frontiers in Global Women's Health, 2025)
BackgroundChad has one of the highest maternal mortality ratios in the world, and low modern contraceptive prevalence. Understanding the barriers and influences on women's decision-making around contraceptive use is critical to reducing the unmet contraceptive need, and thus maternal mortality.MethodsA mixed-methods study was conducted in three districts of Guéra province, Chad, including a longitudinal survey of women, focus group discussions with male and female users and non-users of modern contraceptives, and in-depth interviews with midwives, community health workers, and community leaders.ResultsSurvey participants showed increased knowledge of modern contraceptive methods, and 20.5% reported current modern contraceptive use at endline. Participants described multiple reasons for contraceptive non-use, including that it contradicts with their religious beliefs, community stigma and widespread misconceptions, particularly around long-acting reversible contraceptives. Husbands played a large role in a couple's contraceptive decision-making, as either a major facilitator or barrier depending on the individual.DiscussionOverall, the study's findings suggest that participant awareness of modern contraceptive methods increased. Contraceptive use was more than twice as high as the provincial rate. Given the dominance of injectables within our sample, programs should explore introducing and scaling up community-based distribution of the self-injectable contraceptive (DMPA-SC). The findings highlight the need for more diverse and tailored stigma reduction interventions in the community to promote awareness and reduce misconceptions of modern contraceptives among key groups of people, including men, couples, and religious and other community leaders. Values clarification and attitude training should be considered for all cadres of providers to promote non-discrimination and equity in contraceptive service provision.